O processo de cooperação na psicoterapia de grupo em Gestalt-Terapia - Boris, Georges Daniel Janja Bloc (1992)
Co-operation is defined and analysed from the social-critical perspective of historical and dialectical materialism. The treatment of this question by social psychology is dealt specially in reference to the human small groups as its manifestation space "par excellence". The historical evolution of the practices of group psychotherapies is described and analysed, and the proposal of the Gestalt therapy group is characterized and critically considered from the personal life and the inherited sources and influences of its creator, Frederick (Fritz) Perls. The occurence of co-operative processes in Gestalt groups is investigated. These groups are realized as mediating instances between the individual and society. The psychotherapist role is delimited from the phenomenological and existential perspective. The social-pedagogical tasks and purposes of the group Gestalt therapist are defined in terms of the facilitation of co-operative attitudes, and are described by the analysis of a group psychotherapy process in this approach. In conclusion, the necessary categories, propositions and emphases to the facilitation of co-operation in Gestalt "living" and psychotherapy groups are pointed out.